An assessment of parental knowledge and practices related to pediatric liquid medications and its impact on oral health status of their children - Athimuthu Anantharaj; Praveen Prasanna; Prathibha Rani Shankarappa; Ananya Rai; Selabh Shivram Thakur; Rajeshkrishna Malge (Wolters Kluwer Medknow Publications, 2014)
Background: Pediatric liquid medications (PLM) are the preferred form of medication for young children and contain 'hidden sugars' that increase their cariogenic potential especially in high risk patients. Aims: To assess the general practices followed by parents in the use of common Pediatric liquid medications (PLM), knowledge of dosages, frequency of consumption, side effects and impact on oral health. Settings and Design: The sample comprised of the parents of children visiting the Department of Pediatric and Preventive Dentistry D.A. Pandu Memorial R.V. Dental College, Bangalore. The parents of children up to 8 years of age who preferred liquid medication were included in the study. Subjects and Methods: Questionnaire provided to the parents visiting the Department of Pedodontics and Preventive Dentistry, D.A.P.M.R.V. Dental College, Bangalore. Statistical analysis used: Results are presented in the form of n and % Results: The parental knowledge about PLM use is limited and the oral health of children on frequent use of PLM's is adversely affected especially in high risk patients. Conclusions: Inadvertent and injudicious use of PLM's should be avoided. The parents should be well informed about their usage, side effects and alternate options available.